(untitled) (Indianapolis, IN, 2004)
CCNP Practical Studies: Remote Access (CCNP Self-Study) prepares readers for the CCNP 642-821 BCRAN exam and for workplace challenges in implementing remote access network applications. Designed as a topic-by-topic guide of how to apply remote access concepts in a real network setting, this book is useful in preparing a CCNP candidate for the general exam questions by providing a better understanding of how remote access really works. It is also essential in preparing candidates for the new simulation-based questions that are on the Cisco certification exams. Finally, it serves anyone wanting a guide to real-world application of these concepts, regardless of certification interest. Each chapter includes a review of the applicable technology, and guides the reader through implementation of the technology. This step-by-step process can be executed on a home- or office-based lab, a remote-accessible lab, some networking simulation software programs, or even as a stand-alone guide.
Keywords: Electronic data processing personnel,Routers (Computer networks),Software configuration management,Computer networks; Certification,Examinations,Study guides,Examinations,Study guides,Remote access,Examinations,Study guides